Understanding The Importance of Job Satisfaction for Female Motorcycle Taxi Drivers - Tri Siwi Agustina; Radhiyatul Hayati Putri (Universitas Prasetiya Mulya, 2023)
This study aims to find out more about the effects of the implementation of work flexibility on loyalty and job satisfaction, with work-life balance as mediation among female motorcycle taxi drivers especially in Surabaya, Indonesia. This study is a cross sectional quantitative study with the data collection technique using an instrument in the form of a questionnaire administered to 127 female XYZ’s motorcycle taxi drivers. This study used the path analysis as the data analysis technique to test the research hypothesis. The results showed that work flexibility has significant direct effects on loyalty, job satisfaction and work-life balance among women as motorcycle taxi drivers. The work-life balance did not mediate the effect of work flexibility on the loyalty and job satisfaction among women as motorcycle taxi drivers.